A culture‐independent approach to understanding the role of soil fungal communities in Bromus tectorum stand failure. Issue 1 (3rd February 2021) - Ricks, Nathan J.; Williamson, Taryn; Meyer, Susan E.; Chaston, John M.; Coleman, Craig E.
Abstract: Cheatgrass ( Bromus tectorum L.) is an invasive annual grass (Poaceae) that has colonized large portions of the Intermountain West. Cheatgrass stand failures have been observed throughout the invaded region, the cause of which may be related to the presence of several species of pathogenic fungi in the soil or surface litter. In this metabarcoding study, we compared the fungal communities between sites that have and have not experienced stand failure. Samples were taken from the soil and surface litter near Winnemucca, Nevada, and in Skull Valley, Utah. Our results show distinct fungal communities associated with stand failure based on both geography and sample type. In both the Winnemucca and Skull Valley surface litter, there was an elevated abundance of the endophyte Ramimonilia apicalis in samples that had experienced a stand failure. Winnemucca surface litter stand failure samples had an increased abundance of a potential pathogen in the genus Comoclathris . Skull Valley surface litter stand failure samples had an increased abundance of an undescribed new species in the Rustroemiaceae family which is responsible for the so‐called bleach blonde syndrome in cheatgrass, while the soils had an increased abundance of potential pathogens in the genera Olpidium and Monosporascus . Abstract : Metabarcoding via targeted ITS sequencing was used to characterize fungal communities in cheatgrass soils affected by stand failure in multiple areas. Analysis of the data confirmed key differences in the overall community composition between native communities and those affected by stand failure. Several identified fungal pathogens warrant further investigation to determine whether they are causal agents of stand failure.